2009
DOI: 10.1159/000220345
|View full text |Cite
|
Sign up to set email alerts
|

Injecting, Sexual Risk Behaviors and HIV Infection in Young Cocaine and Heroin Users in Spain

Abstract: Aim: To evaluate differences between young cocaine users and heroin users (HUs) regarding the prevalence of sexual and injection risk behavior, and HIV, HCV and HBV infection. Methods: Two community cohorts were recruited in Madrid, Barcelona and Seville; 720 cocaine users, of whom 586 had never used heroin (CUs), and 991 HUs were interviewed. Dried blood spot samples were tested. Results: CUs were less marginalized socially than HUs. Only 0.9% had ever injected versus 64.3%; none had ever injected with borrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
2
12
0
1
Order By: Relevance
“…Despite the low prevalence of STIs observed in this group of IDUs, the respondents reported a high prevalence of sexual risk practices that is similar to that observed in several previous surveys [7] , and among the general population [10] ; therefore, the risk of transmission of HIV and other STIs remains high [8,9,15] . Consistent with other studies, we found a high prevalence of unprotected sex between HIV-serodiscordant stable partners; this underlines the marked possibility of sexual transmission in this group [23] .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite the low prevalence of STIs observed in this group of IDUs, the respondents reported a high prevalence of sexual risk practices that is similar to that observed in several previous surveys [7] , and among the general population [10] ; therefore, the risk of transmission of HIV and other STIs remains high [8,9,15] . Consistent with other studies, we found a high prevalence of unprotected sex between HIV-serodiscordant stable partners; this underlines the marked possibility of sexual transmission in this group [23] .…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, the change in the prevalence of regular condom use has not been as considerable over the years, especially with stable sexual partners (from 26.3% in 1993 to 32% in 2006). The low condom use observed among IDUs in Catalonia is consistent with that reported in other national [7] and international studies [8,9] . Although the use of condoms among IDUs is similar to that observed in the general population [10] , the higher HIV prevalence observed among this group means that a higher risk of HIV transmission exists.…”
Section: Introductionsupporting
confidence: 90%
“…Regular cocaine use, independently of the route of administration, is also associated with accidents and with the transmission of infectious diseases (through unprotected sex) [7]. Recent concerns have also been raised regarding the association between cocaine use and violent crimes in the night-time economy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Używanie kokainy zwiększa również ryzyko urazów w wyniku wypadków i zakażenia chorobami zakaźny-mi, w tym przenoszonymi drogą płciową [43]. W grupie użytkowników kokainy stwierdza się również wysoki wskaźnik współwystępowania innych uzależnień i zaburzeń psychicznych.…”
Section: Leczenie Uzależnienia Od Kokainyunclassified